THE OUTCOMES OF NEUROPHYSIOLOGICAL EXPERIMENTS OF PACLITAXEL-INDUCED PERIPHERAL NEUROPATHY COMBINED WITH 2-ETHYL-6-METHYL-3-HYDROXYPYRIDINE SUCCINATE ADMINISTRATION - Островський, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Paclitaxelis an effective chemotherapeutic agent for solidtumors,but has series of treatment-limiting adverse effects that markedly decrease patients’ quality of life. Peripheral neuropathy is one of these, but currently, there are no proven effective drugs for the prevention or treatment of paclitaxel-induced neuropathic pain (PINP) or chemotherapy-induced peripheral neuropathy (CIPN) in general. 2-ethyl-6-methyl-3-hydroxypyridine succinate is a derivative of succinic acid with neuroprotective, antihypoxic, membrane protective, nootropic, sedative action. We investigated the pharmacological potential of 2-ethyl-6-methyl-3-hydroxypyridine succinate in preventing paclitaxel-induced peripheral neuropathy. Paclitaxel was administered intraperitoneally to random bred male-rats at a dose of 2 mg/kg 4 times every other day which resulted in mechanical allodynia and thermal hyperalgesia. 2-ethyl-6-methyl-3-hydroxypyridine succinate was injected intraperitoneally at a dose of 10 mg/kg within 10 following days after last paclitaxel administration. The signs of PINP (mechanical allodynia and thermal hyperalgesia) were measured within 150 days of experiment using the von Frey filament assay and Hot Plate test, respectively. Our results suggest that 2-ethyl-6-methyl-3-hydroxypyridine succinate administration exerts a protective effect againstpaclitaxel-induced neuropathy by increasing of reduced mechanical withdrawal thresholds (von Frey assay) and reaction latency (Hot Plate test) on the 7th, 14thand 30th days of experiment. These results indicate that 2-ethyl-6-methyl-3-hydroxypyridine succinate attenuates paclitaxel-induced neuropathic pain in rodents and could be a promising therapeutic agent for the management of this intractable disease.